PENGABDIAN DALAM BENTUK SOSIALISASI DAN PENGAJARAN KEPADA MASYARAKAT DI DESA BELUMBANG TABANAN BALI - Susila, I Made Gede Darma; Ni Luh Putu Sri Widhiastuty; Luh Gede Putri Kusuma Pekerti; Ida Ayu Karina Putri; Saortua Marbun; James Adolft Paparang (Synergy and Society Service, 2024)
In annual activities, community service must be carried out by the campus in fulfillment of its obligation to transfer academic knowledge to the community. Problems in the field are usually not in accordance with the theory that has been studied, so it is necessary to have real learning for students. This real work lecture activity helps lecturers and students collaborate together in solving problems in the village. The location chosen was Belumbang Tourism Village, Tabanan Bali. There are several obstacles that occur, especially the new operation of the village as a tourist village. This makes the village head need to prepare the community in tourism activities in the area. One of them is from awareness about tourist attractions in the area. In addition, homestay accommodation is very potential considering that there is only one villa owned by the local community in this area. Therefore, it is important for local communities to be involved in tourism activities in tourist villages. This service activity includes an introduction, main activities and activity outputs. The results of this service include socialization about tourism potential, waste management and homestay accommodation. Then other services in the form of teaching to elementary school students. It is hoped that this activity can continue, to assist the village to be ready to become a tourist village that can compete with other villages.